A Distant Mirror of Debt, Default, and Relief - Carmen M. Reinhart; Christoph Trebesch (Ludwig-Maximilians-Universität München, Volkswirtschaftliche Fakultät, 2014)
We take a first pass at quantifying the magnitudes of debt relief achieved through default and restructuring in two distinct samples: 1979-2010, focusing on credit events in emerging markets, and 1920-1939, documenting the official debt hangover in advanced economies that was created by World War I and its aftermath. We examine the economic performance of debtor countries during and after these overhang episodes, by tracing the evolution of real per capita GDP (levels and growth rates); sovereign credit ratings; debt servicing burdens relative to GDP, fiscal revenues, and exports; as well as the level of government debt (external and total). Across 45 crisis episodes for which data is available we find that debt relief averaged 21 percent of GDP for advanced economies (1932-1939) and 16 percent of GDP for emerging markets (1979-2010), respectively. The economic landscape after a final debt reduction is characterized by higher income levels and growth, lower debt servicing burdens and lower government debt. Also ratings recover markedly, albeit only in the modern period.
urn:nbn:de:bvb:19-epub-21832-5
Keywords: E6; F3; N0; H6; 330